Peran Financial Technology Pada UMKM Kacang Telur Susu Di Desa Rembang Ngadiluwih Kediri: Peningkatan Literasi Keuangan Berbasis Payment Gateway - Eni Susilowati; Binti Ma’rifah Zulfa; Wafa Aprilia; Dinnii Mafaatihal Asnaa (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
Advances in financial technology will greatly affect society in terms of cashless transactions. This change in the way people transact is known as the phenomenon of a cashless society. Although most people still use cash transactions, there are also those who are starting to use cashless. The emergence of this cashless social phenomenon is one of the roles of financial technology. Fintech services are aimed at millennials who often use the internet. Cashless shopping or transactions are becoming popular among millennials. They are used to using electronic devices such as debit cards, credit cards or electronic money. These developments can bring convenience in financial transactions as well as convenience in using smartphones. To avoid these convenience risks, such as fraud, crime and the risk of fraud in fintech, the government must try to maximize non-cash transactions which can then be carried out safely by supporting people's financial literacy. This study aims to understand the role of financial technology in UMKM Peanut Egg Milk in Rembang Village in increasing payment gateway-based financial literacy. Qualitative research method is a research method used with a descriptive approach. This study uses primary data and secondary data in the form of interviews, observation, documentation. The research results obtained are that MSME actors feel facilitated by the role of financial technology because it can provide time efficiency and increase productivity, but many do not understand financial technology.